Beyond Ukraine debating the future of war - Sweijs, Tim 1981-; Michaels, Jeffrey H. (Oxford scholarship online, 2024)
War in the 21st century will remain a chameleon that takes on different forms and guises. This book offers the first comprehensive update and revision of ideas about the future of war since Russia's 2022 invasion of Ukraine. It argues that the war has fundamentally shifted our perspective on the nature and character of future war, but also cautions against marginalising many other parallel trends, types of war, and ways of waging them. World-renowned international experts from the War Studies field consider the impact of the war in Ukraine on the broader social phenomenon of war: they analyse visions of future war; examine the impact of technological innovation on its conduct; assess our ability to anticipate its future; and consider lessons learned for leaders, soldiers, strategists, scholars and concerned citizens